Energy efficient inter-cluster multi-hop communication routing protocol for wireless sensor network based on centralized energy efficient clustering routing protocol - Makda Fekadie Tewelgne; Samuel Asferaw Demilew; Dagne Walle Girmaw (Discover Applied Sciences)
Abstract Wireless sensor network nodes are small, non-rechargeable devices powered by batteries with limited energy supplies. When using multi-hop communication, data is sent over numerous hops before reaching the cluster head that is farthest from the base station. To minimize power consumption and maximize network lifetimes, this study integrates Multi-Hop communication into the Centralized Energy Efficient Clustering Routing Protocol to determine the optimal path for inter-cluster multi-hop communication between a source (cluster head) and a destination (base station). According to the simulation findings, the suggested algorithm outperforms both the Multi-Hop Technique for the Improvement of Low-Energy Adaptive Clustering Hierarchy Protocol and Energy Efficient Multi-Hop Routing using Genetic Algorithm. The proposed algorithm performs somewhat better than both Energy Efficient Multi-Hop Routing using Genetic Algorithm and Multi-Hop Technique for the Improvement of Low-Energy Adaptive Clustering Hierarchy Protocol in terms of normalized average energy consumption, network lifetime, and packet delivery ratio. The suggested approach is assessed using a MATLAB simulator and contrasted with other similar approaches. Simulations were conducted in a 300 × 300 m2 area with 200 nodes, a base station at (100,100), a round length of 500 s, and an initial node energy of 100 J. Key energy parameters include ETX = ERX = 30 nJ/bit, Efs = 10 nJ/bit/m2, and Emp = 30 nJ/bit/m4. In comparison with Multi-Hop Transmission, the simulation results demonstrated that Energy-Efficient Hierarchical Multi-Hop Routing using Genetic Algorithm improved normalized average energy usage by an average of 5.5 percent and 2.5 percent, packet delivery ratio by an average of 4.1 percent and 2.5 percent, and 3.5 percent and 4.2 percent, respectively.